The archaeological context of recent archaeomagnetic research in Zimbabwe - Huffman, Thomas N.; Manyanga, Munyaradzi; Tarduno, John A.; Watkeys, Michael K. (Southern African Humanities, 2018)
Archaeomagentic research in the Mount Buhwa area of south-central Zimbabwe focused on a Silver Leaves village (2030CB19) and the famous Gokomere site of Mabveni (2030AD5). At both sites, in situ daga features were selected for sampling. These features were the remains of granaries whose burnings correlate with known droughts. The droughts, ceramics and radiocarbon dates place the two occupations in different phases of the Early Iron Age?early fifth and late seventh centuries respectively. Despite the time difference, both sites yielded evidence for interaction with people making Bambata pottery. The rich iron ores attracted faming peoples throughout the Iron Age and interaction was probably common. KEY WORDS: Bambata pottery, Buhwa, droughts, interaction, Mabveni, paleomagnetism, Zimbabwe.